2020
DOI: 10.1080/25741292.2020.1759761
|View full text |Cite
|
Sign up to set email alerts
|

Experimental governance? The emergence of public sector innovation labs in Latin America

Abstract: Public sector innovation labs are becoming an increasingly visible instrument in public sector innovation and experimentation. Proponents of these labs claim they can play an important role in addressing pressing social challenges, changing government structures and thereby shaping ideas and practices of future governance. Whilst some research has been carried out on public innovation labs, the focus of inquiry has been primarily on the emergence, models and activities of labs in Europe and North America. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 17 publications
0
23
0
9
Order By: Relevance
“…Scholars have studied PSI units by distinguishing them under categories such as organisational models, government levels, institutional relationships, approaches used, and operational modes (Gryszkiewicz et al, 2016;Rodríguez, 2018;Schuurman & Tõnurist, 2017;Tõnurist et al, 2017;Williamson, 2015a). Moreover, PSI units have been investigated according to their geographical sphere in areas such as Europe (Fuller & Lochard, 2016), Australia and New Zealand (McGann, Lewis, et al, 2018), and Latin America (Acevedo & Dassen, 2016;Ferreira & Botero, 2020). While the examined labs employ different methodological approaches, a generic "design-led" or "designerly" approach reflects in some of these characterisations Vaz & Prendeville, 2019).…”
Section: Innovation Units and Design Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have studied PSI units by distinguishing them under categories such as organisational models, government levels, institutional relationships, approaches used, and operational modes (Gryszkiewicz et al, 2016;Rodríguez, 2018;Schuurman & Tõnurist, 2017;Tõnurist et al, 2017;Williamson, 2015a). Moreover, PSI units have been investigated according to their geographical sphere in areas such as Europe (Fuller & Lochard, 2016), Australia and New Zealand (McGann, Lewis, et al, 2018), and Latin America (Acevedo & Dassen, 2016;Ferreira & Botero, 2020). While the examined labs employ different methodological approaches, a generic "design-led" or "designerly" approach reflects in some of these characterisations Vaz & Prendeville, 2019).…”
Section: Innovation Units and Design Practicementioning
confidence: 99%
“…While initially design consultancies worked with the public sector mainly in developing service design projects (Bason, 2018, pp. 171-178), in a second evolutionary phase innovation units were created to work on more profound public units, these have received multiple labels 1 as innovation labs (Bason, 2010;Gryszkiewicz, Lykourentzou, & Toivonen, 2016;Tõnurist et al, 2017;Vibeke Carstensen & Christian, 2012), public sector innovation labs (PSI labs) (Ferreira & Botero, 2020;, policy labs (Fuller & Lochard, 2016;Vaz-Canosa, 2021), public innovation labs (Junginger, 2014a), government innovation labs (Bason & Schneider, 2014;Selloni & Staszowski, 2013), innovation teams (i-teams) (Puttick, Baeck, & Colligan, 2014) and public sector innovation units (PSI units) . Moreover, scholars have concluded that design's major contribution to policy happens in the implementation of public services and programs (Bason & Schneider, 2014;Hermus et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…Labs face challenges in moving their agenda forward to implementation. This is often a consequence of tepid or changeable senior level bureaucratic or political support (Ferreira and Botero 2020: 156; Lewis 2020: 6; Tõnurist, Kattel, and Lember 2017: 1468‐69; Olejniczak et al 2020).…”
Section: Challenges For Innovation: Canadian Experience In Global Contextmentioning
confidence: 99%
“…In the case of Latin American labs, it was observed that the need to be “aligned with administrative mandates” (Ferreira and Botero 2020: 160). PIL autonomy is seen as a critical lab characteristic in overcoming deep‐seated government risk aversion.…”
Section: Challenges For Innovation: Canadian Experience In Global Contextmentioning
confidence: 99%
“…There are recent efforts being made to evaluate the work of labs, but there is still little research in the Brazilian and broader Latin American context. According to Ferreira and Botero (2020), labs in Latin America face particular complexities and challenges, such as the needs to work under budgetary constraints, to weave regional networks, and to pay attention to institutional agendas and transitions in public administration, while also being accountable to different levels of society. Additionally, a research conducted on Latin American labs by Acevedo and Dassen (2016) pointed out that a distinctive feature of these labs, in comparison to other regions, is the emphasis given to actions related to transparency and citizen participationdemands arising from democratization processes after periods of dictatorship and less focus on carrying out team impact assessments.…”
Section: Introductionmentioning
confidence: 99%